Atom‐Transfer Radical Addition to Unactivated Alkenes by using Heterogeneous Visible‐Light Photocatalysis. Issue 22 (5th October 2017) - Mao, Liang‐Liang; Cong, Huan
Abstract: Heterogeneous visible‐light photocatalysis represents an important route toward the development of sustainable organic synthesis. In this study visible light‐induced, heavy metal‐free atom‐transfer radical addition to unactivated terminal olefins is carried out by using the combination of heterogeneous titanium dioxide as photocatalyst and a hypervalent iodine(III) reagent as co‐initiator. The reaction can be applied to a range of substrates with good functional‐group tolerance under very mild conditions. In addition to a number of commonly used atom‐transfer reagents, the relatively challenging chloroform is also suitable. Abstract : Shedding visible light on the heterogeneous photocatalyst titanium dioxide in the presence of a catalytic hypervalent iodine(III) reagent has been found as an effective method to initiate a broad range of atom‐transfer radical addition reactions to unactivated alkenes under mild and heavy metal‐free conditions.